Resfriamento transverso para um feixe atômico de estrôncio através de uma melaça ótica - Camargo, Gabriel Errera de Oliveira (2018)
The project aims to understand the interaction behavior of an atomic beam of 88Sr strontium atoms with an optical molasses to optimize the loading of a magneto-optical trap. This system depends on several parameters that can be controlled in the laboratory, such as the power of the laser that originates the molasses, the speed of propagation of the atoms, and laser detuning. To analyze the problem, a computational model was used where a numerical integration method was used to describe the system configurations and thus explore the main characteristics of gain and efficiency in order to find the parameters that maximize the efficiency of the molasses.